From presential education to the adoption of emergential remote education as a result of Covid-19: teaching experience in academic clothing modeling activities (ModaPalavra e-periódico, 2021)
COVID-19 caused a pandemic that has been altered in several human activities - among them Fashion teaching. Adaptations had to be made to continue offering quality education to undergraduate students - regardless of the access possibilities that each student had. The present work presents the changes resulting from the planning of remote didactic activities in the teaching of clothing modeling about classroom teaching.
Keywords: teaching fashion; covid-19; patternmaking for fashion design; remote teaching